Embodied Affect for Real-World Human-Robot Interaction - Canamero, Lola (2020 15th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2020)
The potential that robots offer to support humans in multiple aspects of our daily lives is increasingly acknowledged. Despite the clear progress in social robotics and human-robot interaction, the actual realization of this potential still faces numerous scientific and technical challenges, many of them linked to difficulties in dealing with the complexity of the real world. Achieving real-world human-robot interaction requires, on the one hand, taking into account and addressing real-world (e.g., stakeholder's) needs and application areas and, on the other hand, making our robots operational in the real world. In this talk, I will address some of the contributions that Embodied Artificial Intelligence can make towards this goal, illustrating my arguments with examples of my and my group's research on HRI using embodied autonomous affective robots in areas such as developmental robotics, healthcare, and computational psychiatry. So far little explored in HRI, Embodied AI, which started as an alternative to "symbolic AI" (a "paradigm change") in the way to conceive and model the notion of "intelligence" and the interactions of embodied agents with the real world, is highly relevant towards achieving "real-world HRI", with its emphasis on notions such as autonomy, adaptation, interaction with dynamic environments, sensorimotor loops and coordination, learning from interactions, and more generally, as Rodney Brooks put it, using and exploiting the real world as "its own best model".